2021
DOI: 10.1002/rob.22006
|View full text |Cite
|
Sign up to set email alerts
|

Canopy density estimation in perennial horticulture crops using 3D spinning lidar SLAM

Abstract: We propose a novel, canopy density estimation solution using a three-dimensional (3D) ray cloud representation for perennial horticultural crops at the field scale. To attain high spatial and temporal fidelity in field conditions, we propose the application of continuous-time 3D SLAM (simultaneous localization and mapping) to a spinning lidar payload (AgScan3D) mounted on a moving farm vehicle. The AgScan3D data are processed through a Continuous-Time SLAM algorithm into a globally registered 3D ray cloud. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In [101] researchers have developed a canopy density estimation at four separate locations in South Australia using AgScan3D, a mobile vehicle-mounted 3D spinning LiDAR system, to generate a globally registered ray cloud. The AgScan3D is embedded in the rear of a Kubota farm vehicle and consists of a 3D spinning LiDAR, 3DM-Gx3 IMU and a GPS unit.…”
Section: Robotic Applications In Agriculture For Yield Estimation Andmentioning
confidence: 99%
“…In [101] researchers have developed a canopy density estimation at four separate locations in South Australia using AgScan3D, a mobile vehicle-mounted 3D spinning LiDAR system, to generate a globally registered ray cloud. The AgScan3D is embedded in the rear of a Kubota farm vehicle and consists of a 3D spinning LiDAR, 3DM-Gx3 IMU and a GPS unit.…”
Section: Robotic Applications In Agriculture For Yield Estimation Andmentioning
confidence: 99%
“…Similar work by Nellithimaru and Kantor (2019) presented a method to count fruits and estimate yield and used SLAM combined with Deep Learning techniques to accurately reconstruct the features of grapes fitting with spheres. T. Lowe et al (2021) proposed a novel, canopy density estimation solution using a 3D ray cloud representation for perennial horticultural crops at the field scale. In the proposed method, the AgScan3D (a spinning Lidar payload) data are processed through a Continuous‐Time SLAM algorithm into a globally registered 3D ray cloud.…”
Section: Applications In Agriculturementioning
confidence: 99%
“…Authors in [21], found GMapping to be the most reliable among KartoSLAM [22] and Google-Cartographer [23] although, these algorithms are considered to be efficient only on planar fields. In more recent work described in [9], a SLAM method based on a 3D Lidar data fused with GPS measurements, created 3D maps for the canopy density estimation. The method exhibited accurate results for long travelled distance.…”
Section: A Mapping and Localization In Vineyardsmentioning
confidence: 99%
“…Some approaches focus on the use of cameras in GPS-denied environments [6], [7], [8] to incrementally create a map relied on vineyards structured features. High resolution 3D Lidar sensors are also used to provide dense vineyards reconstruction [9], yet the high-cost of such sensors still hinders the adoption of such solutions. Semantic SLAM methods have also been presented, tailored to vineyards mapping needs, but tested on limited ranges and data [10], mainly due to excessive demands on computational resources.…”
Section: Introductionmentioning
confidence: 99%